Effects of thermal pre-treatment and variables of production on properties of OSB panels of Pinus taeda - Farinassi Mendes, Rafael; Bortoletto Júnior, Geraldo; Ferreira de Almeida, Natalie; Gabriella Surdi, Paula; Najm Barbeiro, Isabela (Maderas. Ciencia y Tecnología, 2025)
The main objective of this study was to compare the effect of thermal pre-treatment in particles of strand type with the effect of variables of production on physical-mechanical properties of OSB panels, aiming to improve their dimensional stability. The experimental design consisted on five treatments with the assessment of two temperatures of thermal treatment on particles (200 and 240°C) during 60 minutes; the increase of adhesive content, the application of paraffin in different treatments and a control treatment. For each treatment three panels with Phenol-Formaldehyde adhesive were produced. The cycle of pressing panels was: pressure of 3.5 MPa and temperature 160°C during 8 minutes. Analyzing the results of tests it was possible to conclude that: the thermal treatment of particles at 200°C promoted a negative effect on physical and mechanical properties, while thermal treatment of particles at 240°C promoted a significant improvement on physical properties and reduction of mechanical properties. The increase on adhesive content resulted in a significant improvement of WA24h, and the application of paraffin improved the WA2h and TS2h of panels, however such treatments were not so efficient on keeping the dimensional stability of OSB panels as a thermal treatment applied on particles at 240°C.